2005
DOI: 10.1128/jb.187.15.5387-5396.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Antimicrobial Peptide Resistance in Neisseria meningitidis

Abstract: Cationic antimicrobial peptides (CAMPs) are important components of the innate host defense system against microbial infections and microbial products. However, the human pathogen Neisseria meningitidis is intrinsically highly resistant to CAMPs, such as polymyxin B (PxB) (MIC > 512 g/ml). To ascertain the mechanisms by which meningococci resist PxB, mutants that displayed increased sensitivity (>4-fold) to PxB were identified from a library of mariner transposon mutants generated in a meningococcal strain, NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
201
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(210 citation statements)
references
References 70 publications
6
201
1
2
Order By: Relevance
“…8A). A similar observation was reported by Tzeng et al (16) in studies with an lptA mutant of N. meningitidis, and based on the capacity of PMB to differentially neutralize modified and unmodified lipid A, we hypothesized that host-derived CAMPs may contribute to the differences in the inflammatory potentials of wild-type and lptA mutant gonococci observed in (open bars) gonococci was incubated with PMB (10 g/ml) or 10 g of CRAMP-38, human LL-37, or lysozyme and then tested for its capacity to induce NF-B expression in MEFs or bind to the LAL reagent. (A) SEAP activity produced by MEFs; (B) LAL activity.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…8A). A similar observation was reported by Tzeng et al (16) in studies with an lptA mutant of N. meningitidis, and based on the capacity of PMB to differentially neutralize modified and unmodified lipid A, we hypothesized that host-derived CAMPs may contribute to the differences in the inflammatory potentials of wild-type and lptA mutant gonococci observed in (open bars) gonococci was incubated with PMB (10 g/ml) or 10 g of CRAMP-38, human LL-37, or lysozyme and then tested for its capacity to induce NF-B expression in MEFs or bind to the LAL reagent. (A) SEAP activity produced by MEFs; (B) LAL activity.…”
Section: Resultssupporting
confidence: 79%
“…PEA decoration of heptose II of the oligosac-charide core of the lipooligosaccharide (LOS) ␤-chain, in contrast, reduces resistance to PMB in Neisseria meningitidis but has no effect in N. gonorrhoeae. The presence of a lipid A PEA moiety also increases N. gonorrhoeae resistance to complement-mediated killing (15,16) but does not affect the serum resistance of N. meningitidis. We recently demonstrated that an lptA mutant of N. gonorrhoeae strain FA1090 was attenuated during experimental urethral infection of male subjects and cervicovaginal infection of female mice (17), which strongly supports the protective role of this lipid A modification during infection.…”
mentioning
confidence: 99%
“…An update of the nomenclature for all Neisserial lipid A PEA transferase enzymes will be announced on PubMLST (pubmlst.org/)]. Mutants of NmEptA increase bacterial sensitivity to CAMPs (12), resulting in attenuation in mice and human models of infection (13). EptA catalyzes the transfer of PEA from phosphatidylethanolamine (PE), via a PEA-enzyme intermediate, to the 1 and 4′ headgroups of the lipid A of lipooligosaccharide (SI Appendix, Scheme S1).…”
Section: Significancementioning
confidence: 99%
“…Katyonik antimikrobiyel proteinler 3 temel kategoride sınıflandırılırlar. Bunlar prolin bakımından zengin lineer proteinler, α-heliks formundaki lineer proteinler ile sistein içeren  tabaka proteinlerdir 3,4 .…”
Section: Katyonik Antimikrobiyel Proteinlerunclassified